Management System Performance of the Catholic Health Organization in Cameroon: An Integrative Literature Review - Eugénie Yvette Nga Ebolo; Benjamin Alexandre Nkoum (Research Highlights in Disease and Health Research Vol. 8, 2023)
Although health outcomes have improved in low- and middle-income countries (LMICs) in recent decades, a new reality is within reach. Changing health needs, rising public expectations and ambitious new health goals require health systems to deliver better outcomes. In many developing countries, the functioning of health systems is one of the main obstacles to access to essential care. The Catholic Organization for Health in Cameroon (OCASC) is not immune to these scourges that undermine health service organizations. An exploratory survey conducted in April 2021, among the coordination team of this body, highlights difficulties in the supply of medicines and medical consumables; obtaining the information necessary for decision-making; instability of human resources; of users’ inaccessibility to health services. All these elements are indicative of a problem of managerial limits of this health subsystem, and for which an audit review is necessary before any reform measure is adopted. Also, this literature review - whose objective was to draw up a state of knowledge on the audit of the management system of a health system - was conducted based on thirty-five (35) studies selected. Studies that have revealed that the audit of the management system of a health system is not simple and that its practice requires the appropriation of basic tools that the actors involved must master. In addition, the idea of evaluating a health organization is based on the principle of optimizing its performance with a view to effective management. And given the legitimate differences that may exist, in terms of approaches and objectives, it is up to the researcher to choose the precise form of evaluation tool/device that would best achieve the intended objective.